KOMPETENSI SOSIAL KEPALA SEKOLAH TERHADAP KINERJA GURU DI TK BUNGA WINAYA KECAMATAN CIRACAP KABUPATEN SUKABUMI (STUDI KASUS DI TK BUNGA WINAYA) - Evi Depriyani; Elnawati, Asep Munajat (CAPITALIS: JOURNAL OF SOCIAL SCIENCES, 2024)
The success of a nation's development is largely determined by its education system. The educational process is carried out mainly by schools. In most cases, the learning process is the first step. Success is largely determined by a person's level of emotional intelligence. Individual success in life is not influenced by intellectual quotient (IQ). The aim of this research is first, to find out how the principal's implementation of social competence affects teacher performance. Second, to find out how the performance of teachers at Bunga Winaya Kindergarten, Ciracap District, Sukabumi Regency. This research uses a qualitative method with a case study research design. The results of the research show that the implementation of the kindergarten principal's social competence affects teacher performance. Act as a leader who has a clear vision and mission and has a good personality and is able to influence or encourage teachers to improve their abilities. Act as a manager who manages all kindergarten programs and their sustainability. Receiving support from various parties, especially from the Foundation, teachers and parents as well as a conducive environment.